Missing the Mark? A Two Time Point Cohort Study Estimating Intestinal Parasite Prevalence in Informal Settlements in Lima, Peru - Michael Townsend Cooper MD; Rapha A. Searing MD; David M. Thompson PhD; David Bard PhD; Hélène Carabin DVM, PhD; Carlos Gonzales MD; Carmen Zavala BS; Kyle Woodson MD; Monique Naifeh MD (SAGE Publishing, 2017)
Objectives: The World Health Organization's (WHO) recommendations list Peru as potentially needing prevention of soil-transmitted helminthiasis (STH). Prevalence of STH varies regionally and remains understudied in the newest informal settlements of the capital city, Lima. The purpose of this study was to evaluate the need for Mass Drug Administration (MDA) of antiparasitic drugs in the newest informal settlements of Lima. The aim of this study was to estimate the season-specific prevalence of STH to determine if these prevalence estimates met the WHO threshold for MDA in 3 informal settlements. Methods : A 2 time point cohort study was conducted among a sample of 140 children aged 1 to 10 years living in 3 purposively sampled informal settlements of Lima, Peru. Children were asked to provide 2 stool samples that were analyzed with the spontaneous sedimentation in tube technique. The season-specific prevalence proportions of MDA-targeted STH were estimated using a hidden (latent) Markov modeling approach to adjust for repeated measurements over the 2 seasons and the imperfect validity of the screening tests. Results : The prevalence of MDA targeted STH was low at 2.2% (95% confidence interval = 0.3% to 6%) and 3.8% (95% confidence interval = 0.7% to 9.3%) among children sampled in the summer and winter months, respectively, when using the most conservative estimate of test sensitivity. These estimates were below the WHO threshold for MDA (20%). Conclusions : Empiric treatment for STH by organizations active in the newest informal settlements is not supported by the data and could contribute to unnecessary medication exposures and poor allocation of resources.